(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2026)
Poetry is the result of an author’s creative impulse. The language of the poetry is among the most creative compared to other types of linguistic expression. Hence, the distinctive lexical properties of poetry represent a constant research challenge. In poetry, all deviations from the linguistic norm are accepted. It is a medium in which authors’ creativity is fully expressed, leading to great diversity in lexical usage. The aim of this research is to provide an overview of the lexical richness found in contemporary Macedonian poetry, including neologisms, archaisms, Turkisms, foreign loanwords, and poetisms. The paper examines the wide range of lexemes in the works of seven female authors who represent contemporary Macedonian poetry. By analysing the excerpted corpus, we conclude that each author possesses an individual poetic style and abundant linguistic expression.